Ion runaway in magnetized plasmas - Embréus, Ola (My University, 2014)
It has been suggested that ions accelerated by static electric fields (so-called runaway ions) in magnetized plasmas could explain experimental observations of heavy ion abundances in solar ares and excitation of Alfvenic instabilities during disruptions in fusion plasmas. However, limitations of previous analytic work have prevented definite conclusions. This has motivated a numerical study of the ion kinetic equation with strong electric fields in magnetized plasmas. In this work the numerical tool CODION (COllisional Distribution of IONs) is developed. It builds upon the existing code CODE, a solver of the electron kinetic equation. CODION solves the initial value problem for the 2-dimensional non-relativistic linearized Fokker-Planck equation in velocity space with a spectral-Eulerian discretization scheme, allowing arbitrary plasma composition and explicitly time-varying electric fields and background plasma parameters. The model is applied to a range of physical scenarios, and 2D ion velocity space distribution functions have been obtained. In particular, the model has been applied to investigate under which conditions ions will be accelerated in fusion plasmas characteristic for the TEXTOR, JET and ITER tokamaks. Typical time scales and required electric fields for ion acceleration have been determined for various plasma compositions, ion species and temperatures, and the potential for toroidal Alfven eigenmodes (TAE) to be excited during disruptions considered. The effect on ion acceleration of various models for self-collisions has been investigated. Results show that during standard operation of fusion experiments, ions will not be accelerated by the runaway mechanism. During typical disruptions it is shown that ions are unlikely to be accelerated, although it could potentially happen under unusual circumstances. It is shown that experimentally observed TAE activity can not be explained by the ion runaway mechanism considered in this work. The utility of CODION for heavy ion acceleration in solar ares is demonstrated, with acceleration rates of various ion species evaluated for one representative scenario.
Keywords: Annan teknik; Grundläggande vetenskaper; Hållbar utveckling; Energi; Other Engineering and Technologies; Basic Sciences; Sustainable Development; Energy